Understanding Local Adaptation to Prepare Populations for Climate Change. (30th November 2022) - Meek, Mariah H; Beever, Erik A; Barbosa, Soraia; Fitzpatrick, Sarah W; Fletcher, Nicholas K; Mittan-Moreau, Cinnamon S; Reid, Brendan N; Campbell-Staton, Shane C; Green, Nancy F; Hellmann, Jessica J
Abstract: Adaptation within species to local environments is widespread in nature. Better understanding this local adaptation is critical to conserving biodiversity. However, conservation practices can rely on species' trait averages or can broadly assume homogeneity across the range to inform management. Recent methodological advances for studying local adaptation provide the opportunity to fine-tune efforts for managing and conserving species. The implementation of these advances will allow us to better identify populations at greatest risk of decline because of climate change, as well as highlighting possible strategies for improving the likelihood of population persistence amid climate change. In the present article, we review recent advances in the study of local adaptation and highlight ways these tools can be applied in conservation efforts. Cutting-edge tools are available to help better identify and characterize local adaptation. Indeed, increased incorporation of local adaptation in management decisions may help meet the imminent demands of managing species amid a rapidly changing world.